Climate Events Synchronize the Dynamics of a Resident Vertebrate Community in the High Arctic - Hansen, Brage Bremset; Grøtan, Vidar; Aanes, Ronny; Sæther, Bernt-Erik; Stien, Audun; Fuglei, Eva; Ims, Rolf Anker; Yoccoz, Nigel; Pedersen, Åshild Ønvik (Science, 2013)
Accepted manuscript version. Published version available at https://doi.org/10.1126/science.1226766 . Copyright © 2018 The Authors, some rights reserved; exclusive licensee American Association for the Advancement of Science. No claim to original U.S. Government Works. Recently accumulated evidence has documented a climate impact on the demography and dynamics of single species, yet the impact at the community level is poorly understood. Here, we show that in Svalbard in the high Arctic, extreme weather events synchronize population fluctuations across an entire community of resident vertebrate herbivores and cause lagged correlations with the secondary consumer, the arctic fox. This synchronization is mainly driven by heavy rain on snow that encapsulates the vegetation in ice and blocks winter forage availability for herbivores. Thus, indirect and bottom-up climate forcing drives the population dynamics across all overwintering vertebrates. Icing is predicted to become more frequent in the circumpolar Arctic and may therefore strongly affect terrestrial ecosystem characteristics.